Improving Understanding of the Solar System Concept Through the Application of STEAM Assisted by Augmented Reality (AR) Media - Najwa Safina; Fahmi Fatkhomi; Muriani Nur Hayat (Pascasarjana, Mataram University, 2026)
Teachers struggle to explain abstract concepts, and a lack of supporting facilities in some schools also hinders the implementation of learning media. Low student engagement in learning can lead to misconceptions and a decline in conceptual understanding, which should be the foundation for knowledge acquisition. Therefore, students' understanding plays a crucial role in the learning process, which requires their ability to interpret meaning, master concepts, understand situations, and apply the facts they have learned. This study aims to determine the extent to which students' conceptual understanding increases in the solar system material by implementing STEAM learning assisted by Augmented Reality (AR) media in science learning. The method used is a quasi-experimental with a pretest-posttest control group design. With a purposive sampling technique, the sample was determined with class VII D as the experimental class and VII C as the control class. The instruments used included pretest-posttest questions and documentation, with data analysis carried out using SPSS version 26. The results showed that students' conceptual understanding in the experimental class reached 90.97% (very good category), while the control class was 76.94% (fairly good category). This study shows that the application of STEAM assisted by AR media has a positive impact, namely it is effective in improving students' conceptual understanding of the solar system.